Retrospective study to assess the prevalence of overweight and obese women delivering at tertiary care centre in Pune - Tripathy, Sumeet R.; Rathore, Priyanka; Basarkod, Santosh S.; Bezbaruah, Madhurya; Kaur, Mandeep; Debnath, Sushmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Obesity is a modern-day epidemic affecting women in reproductive age group. Increase in obesity in pregnant women is associated with increased rates of complications. Methods: A retrospective study was conducted based on available hospital data between January 2020 and March 2020. Pregnant women who have had their first visit at this centre before 20 weeks period of gestation were included and were classified into normal body mass index (BMI), overweight and obese. The rates of caesarean delivery, hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM), assisted reproductive techniques (ART) for conception and neonatal intensive care unit (NICU) admissions were studied. Results: A total of 582 pregnant women were included in the study. The estimated prevalence of obesity was 29.3% (n=171) whereas 27.8% (n=162) were overweight. There was statistically significant association seen between obesity and caesarean delivery rates, HDP, NICU admission. Conclusions: The results reveal high prevalence of obesity in pregnant women. There is a need for a comprehensive and clinically effective approach to tackle obesity.